2018
DOI: 10.5433/1679-0359.2018v39n5p2125
|View full text |Cite
|
Sign up to set email alerts
|

Fermentation pattern of tropical grass haylage and digestibility compared to hay in equine diet

Abstract: Hay production is the most common form of forage conservation methods for horse feeding. However, haylage can be an alternative to hay. The present research assessed the nutritional value of Tifton-85 haylage by fermentation pattern, bromatological composition, and apparent digestibility compared to hay in the diet of Quarter Horse mares. Haylage was prepared with 700.0 g of dry matter (DM) kg-1 added with a biological inoculum and was assessed at 1, 3, 7, 14, 28, and 56 days of production. At 14 days, the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…The haylages with 40-50 and 50-60% DM had lower N-NH 3 values. The value obtained in this study was similar to what was found by Costa et al (2018a) which was 1.25% and by Guimarães et al (2019) which was 1.10%, in haylage of Tifton 85 at 56 days of evaluation.…”
Section: Aerobic Stability Ph and N-nh 3 Of The Haylagesupporting
confidence: 92%
See 2 more Smart Citations
“…The haylages with 40-50 and 50-60% DM had lower N-NH 3 values. The value obtained in this study was similar to what was found by Costa et al (2018a) which was 1.25% and by Guimarães et al (2019) which was 1.10%, in haylage of Tifton 85 at 56 days of evaluation.…”
Section: Aerobic Stability Ph and N-nh 3 Of The Haylagesupporting
confidence: 92%
“…During fermentative activities inside the haylage bales, the level of O 2 is reduced and CO 2 is raised by microorganisms, which depends on the species, extent of plant respiration, harvest processes, material wrapping and DM content (Costa et al ., 2018a).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The haylage is based on the dry matter (DM) content after a wilting process, then baled similar to hay and wrapped with plastic films in order to be conserved under anaerobic fermentation. According to Müller (2005) the DM content after wilt exceeds 500 g kg -1 , Costa et al (2018) attributed its definition to a variation of DM from 500 to 750 g kg -1 .…”
Section: Definition Of Haylagementioning
confidence: 99%
“…It should be noted that the pH of the haylage, because it has a high content of dry matter in the confection, limits the capacity of bacterial fermentation, as it does not produce sufficient acid and becomes resistant to the pH drop, this characteristic must be considered along with other factors, such as forage buffer capacity. Therefore, the pattern used to evaluate haylage fermentation parameters should be different from those recommended for silage (COSTA et al, 2018).…”
Section: Main Fermentationsmentioning
confidence: 99%